Industry 5.0 Post Pandemic Transformation: A Study of Challenges to Inclusive Work Environment (Indian Journal of Management and Language (IJML), 2025)
The concept of Industry 5.0 gives a distinctive center and highlights the significance of inquiring about and advancement to back the industry in its long-term benefit to humankind inside planetary boundaries. The concept of industry 5.0 was given by the Japan. They emphasized on advanced technological advancement in each sector for more production and economic upliftment. Industry 5.0 needs to come to hold with the guarantees of progressed digitalization, huge information, and counterfeit insights, whereas accentuating the part these innovations can play to address modern, new prerequisites within the mechanical, societal and natural scene. Unused technologies have the potential to form work environments more comprehensive and more secure for specialists, as well as increment their work fulfillment. Many have lost their job during the pandemic. A large section of our society is not able to cope with innovative techniques. The study will highlight the challenges to inclusive work environments in MNCs in India and suggest measures to face these challenges through empirical research.